Protective Role of Mast Cells in Primary Systemic Vasculitis: A Perspective - Springer, Jason M.; Raveendran, Vineesh V.; Gierer, Selina A.; Maz, Mehrdad; Dileepan, Kottarappat N. (Frontiers in Immunology, 2017)
Mast cells are important cells of the immune system. Although, traditionally considered as key players in allergic and hypersensitivity reactions emerging evidence suggest that mast cells have many complex roles in vascular disease. These include regulation of vasodilation, angiogenesis, activation of matrix metalloproteinases, apoptosis of smooth muscle cells, and activation of the renin angiotensin system. Mast cells are also known to play an immunomodulatory role via modulation of regulatory T-cell (T-reg), macrophage and endothelial cell functions. This dual role of the mast cells is evident in myeloperoxidase anti-neutrophil cytoplasmic antibodies (MPO-ANCA)-mouse model of glomerulonephritis in which mast cell deficiency worsens glomerulonephritis, whereas inhibition of mast cell degranulation is effective in abrogating the development of glomerulonephritis. Our previous work demonstrated that mast cell degranulation inhibits lipopolysaccharide (LPS)-induced interleukin 6 (IL-6) production in mice. This effect was not seen in histamine-1-receptor knockout (H1R-/-) mice suggesting a role for histamine in IL-6 homeostasis. In addition, mast cell degranulation-mediated decrease in IL-6 production was associated with an upregulation of suppressor of cytokine signaling-1 protein (SOCS-1) in the aorta. We propose that mast cells regulate large artery inflammation through T-cells, shifting a primarily Th1 and Th17 toward a Th2 response and leading to enhanced production IL-10, activation Treg cells and the inhibition of macrophage functions.